Analgesic efficacy of serratus anterior plane block v/s thoracic paravertebral nerve block in video-assisted thoracoscopic surgeries: A prospective randomized study - Lalwani, Jaya; Sahu, Sonali; Manghnani, Vritika; Jain Shah, Pratibha (Pain medicine, 2025)
Background: Multimodal analgesia plays a vital role for adequate pain relief in postoperative period including regional nerve blocks in video-assisted thoracoscopic surgeries. The study aims to compare the analgesic efficacy of serratus anterior plane block and thoracic paravertebral nerve block using ultrasound guidance in VATS. Methods: Eighty patients scheduled for VATS under general anaesthesia, aged 18-65 years, ASA grade II & III were randomised to receive either SAP block (Group A) or TPV block (group B) after induction. Intensity of postoperative pain relief at rest & on coughing till 48 hours using VAS score, intraoperative hemodynamic changes, time to 1st rescue analgesia, complications and patient satisfaction score at 24th hour postoperatively were compared. Unpaired t-test and Chi- Square test were used for analysis. A P value less than 0.05 was considered to be statistically significant. Results: At rest, mean VAS scores in group B were slightly higher than group A till 18 hours, but the difference was statistically insignificant. At 24th and 48th hour, mean VAS scores were significantly more in group A than group B. On coughing, mean VAS scores at 12th, 18th, 24th, and 48th hour were significantly higher in group A as compared to group B (p<0.05). Mean time to 1st analgesic requirement was earlier in group A (20.97±4.9 hours) than group B (28.4±9.5 hours) (p<0.001). Both groups were hemodynamically stable with no side effects and no additional analgesic requirement. Patients in both groups at 24th hour were highly satisfied. Conclusion: TPV block provided longer duration of post-operative analgesia both at rest and on coughing with delayed requirement of first rescue analgesia.